Can heterogeneity in ventilation be good? - Costa, Eduardo LV (BioMed Central, 2010)
Selection of the optimal positive end-expiratory pressure (PEEP) to avoid ventilator-induced lung injury in patients under mechanical ventilation is still a matter of debate. Many methods are available, but none is considered the gold standard. In the previous issue of Critical Care, Zhao and colleagues applied a method based on electrical impedance tomography to help select the PEEP that minimized ventilation inhomogeneities. Though promising when alveolar collapse and overdistension are present, this method might be misleading in patients with normal lungs.